MANAJEMEN PERUBAHAN DALAM MEWUJUDKAN MADRASAH BERPRESTASI - Nur Arifah (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2020)
Abstact: The head of the madrasah embodies a madrasah that has achievements with the aim of improving the quality of madrasas nationally and internationally. Where competition is getting tighter, madrasas are progressing rapidly and other madrasas are out of business. These madrasas have a different strategy from other madrasas. This study aims to find out about change management and the implementation of the achievement of madrasas that have been accomplished.